Ski economy and physiological responses while double poling : curved vs. straight poles - Mishica, Christina (2015)
Christina Mishica (2015). Ski economy and physiological responses while double poling: curved vs. straight poles. Department of Biology of Physical Activity, University of Jyväskylä, Master’s Thesis in Exercise Physiology. 57 pp.